PENGARUH KEPEMIMPINAN, SANKSI HUKUM DAN PENGAWASAN TERHADAP KEDISIPLINAN KERJA PEGAWAI PADA DINAS SOSIAL PROVINSI RIAU - Lia Watimah; Dewita Suryati Ningsih; Andewi Rokhmawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study is motivated by the level of employees’ discipline at Service Office of Riau Province which has not been optimal. This problem is caused by their leader who has not given a good example, sanction and good supervision. This study aimed to analyze the influence of leadership, sanction and supervision on employees’ discipline of Service Office of Riau Province. There are three independent variables in this study, namely: leadership, sanction and supervision on employees’ discipline. The data of this study were collected by distributing questionnare to the respondents in which they were selected based on random method. Were processed using SPSS program version 21. In this research can be seen how the effect of leadership, sanction and supervise of working discipline in the Sosial Office of Riau Province. The analytical method used in this study was multiple linear pregression. Based on statistical data analysis, indicators in this study are valid and reliable. The results of the study showed that not all independent variables affect to dependent variables. The result of the research is that only variable sanction has a significant effect on employees’ discipline. Other variables (leadership and supervision) do not have a significant effect on employees’ discipline.Keywords: leadership, legal sanctions, supervision, discipline.